Transnational Advocacy Networks: A Complex Adaptive Systems Simulation Model of the Boomerang Effect. (June 2017) - Bloodgood, Elizabeth A.; Clough, Emily
We examine the costs and benefits of nongovernmental organization (NGO) networking using a complex systems approach and agent-based modeling to simulate the effects of NGOs' efforts to seek influence in policy making at home and abroad. We elaborate on the boomerang model developed by Keck and Sikkink and uncover macro-level effects of multiple NGOs networking for policy influence in multiple states around multiple positions on the same issue simultaneously. The results of our model and simulations lead us to argue that the boomerang effect has interesting unexplored implications for NGO behavior and state policy worthy of further empirical testing. We find that networking is necessary for NGOs to change state policy but leads to a higher likelihood of organizational collapse for NGOs. Although networking leads to policy change, as is well demonstrated within existing literature, our model suggests that efficacy comes at a cost to NGOs, which should make analysts and academics more ambivalent about the advisability of NGO networking.